2007
DOI: 10.1007/s10800-006-9271-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability of spontaneous passive films on high strength Mo-containing stainless steels in aqueous solutions

Abstract: The stability of naturally grown passive films on some Mo-containing stainless steel specimens was examined in aerated and deaerated universal buffer solutions with different pH (2-12) as well as in sulphate and chloride solutions. Open circuit potential (E oc ) and electrochemical impedance spectroscopy (EIS) were used as measuring techniques. In all cases, E oc shifts towards less negative values with time until the potential reaches its steady-state (E ss ) value. The E ss value is found to be more positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 31 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, at any sulfate concentration the OCP of alloy II is always more noble than that for pure Ag. The ennobling of potential signifies additional passivation due to thickening and self-healing of the surface oxide film [15,16]. The behavior of alloy II accords with previous report indicating that the presence of a small amount of tin reduces the corrosion ability of Ag-Sn surface [13].…”
Section: Effect Of Concentrationsupporting
confidence: 83%
“…Furthermore, at any sulfate concentration the OCP of alloy II is always more noble than that for pure Ag. The ennobling of potential signifies additional passivation due to thickening and self-healing of the surface oxide film [15,16]. The behavior of alloy II accords with previous report indicating that the presence of a small amount of tin reduces the corrosion ability of Ag-Sn surface [13].…”
Section: Effect Of Concentrationsupporting
confidence: 83%
“…The increase in the R p values in the presence of different concentrations of PMN, MMN, NBT and MBN indicates reduction in the MS corrosion rate with the formation of adsorbed protective film on the metal-solution interface [47,48]. When the concentration was raised from 200 to 500 ppm, there was a gradual increase in the diameter of each semicircle of the Nyquist plot reflecting the increase in R p values from 27.81 to 163.8, 190.5, 316.8 and 562.0 X cm 2 for PMN, MMN, NBT and MBN, respectively which indicates the adsorption of inhibitor molecules on the metal surface and also increase in stability of inhibitors film adsorbed on the metal surface.…”
Section: Potentiodynamic Polarization Studiesmentioning
confidence: 99%
“…1, it can be concluded that film growth follows a direct logarithmic law (Eq. 1) for which the formation process is the rate-limiting step [13]:…”
Section: Open Circuit Potentialmentioning
confidence: 99%
“…Thus, at pH 11.8 the E st value lies nearly midway between those for PO 3À 4 and HPO 2À 4 solutions and at pH 4.5 E st was found to be higher than that for H 2 PO À 4 medium, while at pH 9.1 it acquires its highest measured value. This implies that pH, as well as nature of the prevailing anions contribute to the spontaneous passivation of AZ91D alloy through possible incorporation of these anions into the lattice structure of the growing film [16], where they are located within the outer part of the passive film [13].…”
Section: Open Circuit Potentialmentioning
confidence: 99%
See 1 more Smart Citation